PREPARATION OF PINEAPPLE LEAF NANOFIBRIL/TIO2 COMPOSITE AS ANTIBACTERIAL ACTIVE PACKAGING MATERIAL - Aditya Pertiwi, Gian
Cellulose nanofibrils and cellulose nanofibril-based composites are renewable biomaterials that are being extensively studied due to their various application potential, for example, in active antibacterial packaging. This type of packaging increases the shelf life and maintains the quality of fresh and processed products. Lignocellulosic biomass is a source of cellulose nanofibrils with superior and unique characteristics. Pineapple leaves are abundant post-harvest waste in Indonesia and are a potential source of cellulose nanofibrils. The challenges in the production of cellulose nanofibrils are the high energy consumption in the mechanical process and the use of corrosive chemicals such as H2SO4 and HCl, as well as toxic materials such as TEMPO as a pretreatment process to reduce energy consumption. The right combination of chemical and mechanical processes is required for optimal cellulose nanofibril production. Organic acid hydrolysis can be an alternative chemical process that is safe and effective. Therefore, in this study, the cellulose nanofibrils isolation of pineapple leaves was carried out through a combination of chemical and mechanical processes, spesifically succinic acid hydrolysis and ultrasonication. In addition, a cellulose nanofibril/TiO2 composite was made as an active antibacterial packaging material. Metal oxides such as TiO2 can act as an effective and safe antibacterial agent in active packaging. The first stage of this research was collecting and drying pineapple leaves in Cikendung Village, Pulosari District, Pemalang Regency, followed by fiber morphology analysis, which included measuring fiber length and diameter. The second stage is the manufacture of pineapple leaf powder and analysis of the chemical components of pineapple leaves, which include water content, lignin, hemicellulose, holocellulose, and alpha cellulose. The third stage is delignification and bleaching of the fiber, with pre-treatment using alkali (2% (w/v) NaOH) and bleaching using 1.7% (w/v) NaClO2. X-Ray Diffraction (XRD) was used to determine the crystallinity of the unbleached and bleached fibers. The fifth stage was hydrolysis of the delignified and bleached fibers using succinic acid (C4H6O4) at various concentrations of 0, 0.1, 0.2, 0.3, and 0.4 mol/L. The next stage is ultrasonication as a mechanical treatment to obtain cellulose nanofibrils. The characterization of cellulose nanofibrils was carried out including morphological characters and elemental composition, using Scanning Electron Microscope- Energy Dispersive X-Ray (SEM-EDX) and crystallinity index using X-Ray Diffraction (XRD). The next stage was the manufacture of cellulose nanofibril/TiO2 composites with various concentrations of TiO2 (5, 10, 15% (w/w)). The physical analysis of the composite includes tensile strength, thickness, brightness, and porosity. The final stage is testing the antimicrobial activity against Escherichia coli and Staphylococcus aureus using the Kirby-bauer method. Succinic acid had a significant effect (P < 0.05) on fiber yield, diameter, and length. The optimal hydrolysis process occurs at 0.3 mol/L succinic acid concentration, resulting in a 45.18% decrease in fiber diameter and a yield of 92.35±1.61%. The hydrodynamic force generated during the ultrasonication process causes cellulose defibrillation to produce nanofibrils. The diameter of the nanofibrils ranged from 25-170 nm with the most dominant was fibrils with sizes of 44-62 nm. The elements detected were C and O, with masses of 50.37% and 49.63%, respectively. The Hydrolysis and ultrasonication processes increased cellulose crystallinity. The crystallinity index of cellulose nanofibrils was higher than that of unbleached and bleached fibers, which was 68.63%. TiO2 nanoparticles in the cellulose nanofibril composite significantly increased the tensile strength, thickness, and brightness of the composite (P < 0.05). TiO2 nanoparticle concentration of 10% (w/w) is effective in increasing the thickness and brightness of the composite. The higher the concentration of TiO2 nanoparticles, the higher the tensile strength. Tensile strength is an important factor in the selection of materials for packaging. Nano TiO2 also had a significant effect (P < 0.05) on porosity, which reflects the permeability of the composite to air. The addition of 5% (w/w) nano TiO2 increased the porosity of the composite but decreased at 10% (w/w) and 15% (w/w). The cellulose nanofibril/TiO2 composite had a significant effect on E. coli (P < 0.05). TiO2 concentrations of 5, 10, and 15% (w/w) increased antibacterial activity as measured by the increased diameter of the inhibition zone, which was 8.0±0.7 mm, 9.7±1.9 mm, and 10.3±2.2 mm, respectively. Statistically, the effect of 10% (w/w) TiO2 was not significantly different from 15% (w/w) TiO2. The cellulose nanofibril/TiO2 composite also had a significant effect on S. aureus. The addition of TiO2 at 5, 10, and 15% (w/w) resulted in an inhibition zone against S. aureus of 7.5±0.7 mm, 8.5±1.5 mm, and 7.9±1.2 mm which statistically were not significantly different. The cellulose naofibril/TiO2 composite had a greater effect on E. coli which is a gram-negative bacterium, compared to S. aureus which is a gram-positive bacterium.